ANALISIS INTERVAL PENGGANTIAN KOMPONEN KNIFE STEEL PADA MESIN CANE KNIFE TEBU DI PABRIK GULA GEMPOLKREP MOJOKERTO - Rizky Pratama Putra; I Nyoman Lokajaya (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
PT. Archipelago Sugar Synergy Sugar Factory Gempolkrep is a company engaged in the production of sugar. Located at Jalan Raya Gempolkrep, Suko Sewu, Kec. Gedek, Kabupaten Mojokerto, Jawa Timur. Sugar factory started operating in 1889 until now. Functionally, Sugar Factory’s work system is divided into two parts, Namely the production process which is carried out every six months and lasts for four until six months. While the remaining six months are used for machine preparation, maintenance and total replacement (Overhaul) on the machine for the next production process. Problems often occur during the milling season, especially in the station area Diffuser. In the subject matter the machine under study is machinery Cane Knife Sugarcane. This is due to the repair or replacement of blades due to damage to the machine causing the production process to stop. When the machine suddenly breaks down during the production process, so that costs in the form of losses due to lost production opportunities can increase. The heavier and more broken blade, the replacement process will take longer. Replacing it too often disrupts the production process and maintenance costs are high. By using the program method Age Replacement expected to provide information about the time to replace the knife on the machine Cane Knife Sugarcane which aims to avoid sudden damage during the milling process. And it is hoped that the company’s maintenance costs will not be high